THE LATE QUATERNARY HYDROLOGICAL HISTORY OF THE SEA OF OKHOTSK AS EVIDENCED BY FORAMINIFERS - Khusid T.A.; Basov I.A. (My University, 1999)
Benthic foraminifers from sediments, which have been obtained at the slope of the Kuril island are in the southeastern part of the Sea of Okhotsk (Core V34-98, depth of 1175 m) and dated by using the AMS radiocarbon technique, were studied. Taxonomic composition, species diversity and: abundance, as well as changes of these characteristics were used to reconstruct main hydrological events in the basin during,the late Pleistocene and Holocene. It is shown that during the last 17000 years, the bottom of Sea of Okhotsk was successively populated by three benthic foraminiferal assemblages different from each other by dominant,;species, such as the Eponides weddellensis, Brizalian spissa, and Bollvina seminuda assemblages. The assemblages characterize particular hydrologic environments and correspond to three main periods of the late Pleistocene-Holocene history of the basin evolution, or to three climatostratigraphic intervals: the terminal stage of the last glaciation (17-12.5 ka), deglaciation stage (12.5-8.5 ka), and last interglacial, or postdeglaciation period (last 8 ka). Changes in the structure of benthic foraminiferal assemblages cue consistent with data on the oxygen isotope composition of their carbonate shells.
Keywords: Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная